A Chart-Based Practical Guideline on the Application of Neutral Grounding Elements for Interconnecting Large-Scale Distributed Energy Resources - Nassif, Alexandre B.; Aguero, Julio Romero (Proceedings of the ... IEEE Power Engineering Society Transmission and Distribution Conference, 2022)
Distributed Energy Resources (DERs) are gaining widespread acceptance across most jurisdictions. As distribution grid operators strive to maximize the interconnection of DERs, they experience new issues that require thorough assessment and mitigation. An emerging issue plaguing electric utilities lie within the intersection of protection and performance grounding. These are strongly interrelated and conflicting subjects that dictate the occurrence of Temporary Overvoltage and the effectiveness of ground overcurrent protection. Currently, there remains a gap in the distribution planning of most jurisdictions in formulating these aspects and adopting simple and practical measures to balance these subjects. This paper develops a simulation-based method to develop a set of practical charts intended to be used as a sizing guideline for neutral grounding elements, which are to be employed in DER step-up transformers. This solution became pivotal to the electrical utility conducting the research and has allowed planning engineers to simplify design and streamline cooperation between the utility and large-scale DER developers.